PERSEPSI SN DAN MR TENTANG PRESIDEN JOKO WIDODO: ANALISIS WACANA TRANSKRIP REKAMAN PERCAKAPAN ‘PAPA MINTA SAHAM’ - Kusno, Ali (Fakultas Ilmu Budaya, Universitas Mulawarman, 2016)
The recording of “Papa Minta Saham“conversation captured the Indonesian society’s attention in the end of 2015. It recorded the conversation between SN and MR profiteering the name of President Jokowi. In addition, another topic of conversation such as both SN and MR’s perception about President Jokowi was also revealed in this recording. This research aims to analyze the perception of SN and MR about President Jokowi’s character. Applying descriptive qualitative method, the language contained in the “Papa Minta Saham” recording was used as the research object. The data and data source were the transcript document and the recording conversation of “Papa Minta Saham”. This research used discourse analysis. The findings showed diverse negative perceptions regarding President Jokowi’s character: stubborn (koppig), difficult to build a mutual understanding, a high level of ego, strong determination, tough and dangerous. Apart from these negative characters, Jokowi is also considered as a kind and brave type of person. Based on the findings, there is an indication that public perception towards President Jokowi’s characters could be different from that of SN and MR. Politicians also speak language containing various strategies that prove the distinction between their public speech and their actual speech. Politicians could change their negative perceptions into positive perceptions as well as their languages to accommodate their interests.Key words: perception discourse analysis, Papa Minta Saham transcript, perception of President Jokowi